Legal Support for The Assessment of An Individual's Understanding of The Consequences of His Actions based on Artificial Intelligence (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Artificial intelligence technologies are currently intensively developing, in including due to the development of technologies of sustainable neural networks and cloud infrastructures computing, fuzzy systems technologies, entropy control, swarm intelligence, evolutionary computing, and more. At the same time, the problem of the almost complete absence of legal regulation and normative technical regulation of the fundamentals, conditions and features of development, commissioning, operation and activities, integration into other systems and control of the use of artificial intelligence technologies. This article is devoted to the study of the specifics of legal regulation use and development of artificial intelligence. Some approaches to the definition of artificial intelligence and the peculiarities of the legislative support of the corresponding sphere, which take place in the scientific literature, are considered, the author's concept of artificial intelligence is developed and presented through the disclosure of its main features. In particular, according to the proposed definition, artificial intelligence is artificially complex a cybernetic computer-software-hardware system with the properties of substantiveness, autonomy, as well as the ability to perceive and analyze data, self-study.